Cutting Words: Priming Self-Objectification Increases Women's Intention to Pursue Cosmetic Surgery. (June 2014) - Calogero, Rachel M.; Pina, Afroditi; Sutton, Robbie M.
We examined whether subtle exposure to sexually objectifying cues increases women's intentions to have cosmetic surgery. Undergraduate women ( N = 116) were randomly assigned to a condition in which they unscrambled sentences containing words associated with sexual objectification, non-self-objectifying physicality, or neutral content. Following a manipulation check of these primes, participants reported their body shame and intentions to have cosmetic surgery in the future. Results revealed that priming a state of self-objectification, compared to the two non-self-objectifying conditions, increased both body shame and intentions to have cosmetic surgery. In a mediational model, the link between self-objectification and intentions to have cosmetic surgery was partially mediated by body shame. Controlling for other key intrapersonal and social motives linked to interest in cosmetic surgery did not alter these patterns. These findings highlight the potential for the consumption of cosmetic surgery to stand as another harmful micro-level consequence of self-objectification that may be perpetuated via subtle exposure to sexually objectifying words, even in the absence of visual depictions or more explicit encounters of sexual objectification.